Eviota piperata, a new gobiid species from Palau (Teleostei: Gobiidae) - Greenfield, David W.; Winterbottom, Richard (Zootaxa, 2014)
A new species of dwarfgoby, Eviota piperata is described from Palau. It belongs to the cephalic sensory-pore system Group II (lacking only the IT pore); has a dorsal/anal-fin formula of 8/8; has some pectoral-fin rays branched; no dark spot over the ural centrum; the male genital papilla is not fimbriate; and the cheek and body are heavily peppered with chromatophores.